Johann Jakob Griesbach: a Re-Evaluation of the Role His Synopsis Played in the Development of His Two Gospel Hypothesis - Lang, Marijke Hélène de (Annali di storia dell' esegesi, 2022)
Although it is often assumed that Johann Jakob Griesbach’s groundbreaking Synopsis (1774) was the basis for the formulation of his Two Gospel Theory (1783), this article will try to prove that in fact the two were unrelated. The Two Gospel Theory did not emerge from the careful study of his synopsis and as an answer to the literary problem of the interrelation of the synoptic gospels, but first and foremost as a response to the problem of the historical reliability of the Gospels, raised by the publication of the work of Hermann Samuel Reimarus (1694-1768).